2010
DOI: 10.5194/acp-10-8803-2010
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the contributions to stratospheric ozone changes from ozone depleting substances and greenhouse gases

Abstract: Abstract.A state-of-the-art chemistry climate model coupled to a three-dimensional ocean model is used to produce three experiments, all seamlessly covering the period 1950-2100, forced by different combinations of long-lived Greenhouse Gases (GHGs) and Ozone Depleting Substances (ODSs). The experiments are designed to quantify the separate effects of GHGs and ODSs on the evolution of ozone, as well as the extent to which these effects are independent of each other, by alternately holding one set of these two … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
46
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 43 publications
8
46
0
Order By: Relevance
“…Above 30 hPa, trends decrease towards zero and become hemispherically symmetric in the multi-model mean. The structure of the trends agrees well with the differences in cumulative ozone columns from the mid-20th to the end of the 21st century shown by Plummer et al (2010). They used sensitivity simulations to attribute these trends almost fully to changes in GHG concentrations, thus validating our method of separating the effects of ODSs and GHGs through linear regression.…”
Section: Height Dependence Of Hemispheric Difference In Return Datessupporting
confidence: 63%
See 1 more Smart Citation
“…Above 30 hPa, trends decrease towards zero and become hemispherically symmetric in the multi-model mean. The structure of the trends agrees well with the differences in cumulative ozone columns from the mid-20th to the end of the 21st century shown by Plummer et al (2010). They used sensitivity simulations to attribute these trends almost fully to changes in GHG concentrations, thus validating our method of separating the effects of ODSs and GHGs through linear regression.…”
Section: Height Dependence Of Hemispheric Difference In Return Datessupporting
confidence: 63%
“…Enhanced efficiencies are found in the SH, where an expansion or shift of the polar vortex provides the conditions for heterogeneous ozone depletion in midwinter north of 60 • S. This effect was noted earlier for southern polar ozone, for example by Plummer et al (2010), who found a nonlinearity of the response of ozone to ODSs in the Antarctic lower stratosphere under changing GHG concentrations. Similarly, Revell et al (2012a) reported an increase of Antarctic lower stratospheric ozone in a scenario with lower GHG concentration increases as compared to the standard REF-B2 simulation.…”
Section: Lower Stratosphere: CL Y Destruction Cyclesmentioning
confidence: 77%
“…More recently, Plummer et al (2010) found that nitrogen species induced large stratospheric ozone losses once the effects of CO 2 -induced stratospheric cooling were removed. In addition, increasing sea-surface temperatures (SSTs) are projected to strengthen the Brewer-Dobson circulation, resulting in a faster removal rate of reservoir nitrogen species from the stratosphere (Cook and Roscoe, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In mixing ratio terms, this gives a rate of ∼ 5-7 ppbv yr −1 . Plummer et al (2010) studied O 3 changes in a model including GHGs (greenhouse gases) and ODSs (ozone-depleting substances). They ran two experiments with a faster Brewer-Dobson circulation, and these two experiments showed, at 10 hPa in the tropics, a decrease in reactive nitrogen and an increase in both O 3 and N 2 O at 10 hPa relative to the experiments with a slower circulation.…”
Section: Introductionmentioning
confidence: 99%